Kontribusi Wanita Hindu Dharma Indonesia Dalam Meningkatkan Sradha dan Bhakti Wanita Hindu Di Kabupaten Kapuas - G.A Melinda; G.A Kristha Adelia Indraningsih (Bawi Ayah: Jurnal Pendidikan Agama dan Budaya Hindu, 2022)
As an effort to support the complex role of women, there is a Forum of Wanita Hindu Dharma Indonesia (WHDI). 5The Organization aims to acomodation the aspirations and creativity of Hindu women so that they can compete in the inter-religion. WHDI kapuas district has a strategic role to participate in creating happy family physically and mentally, as well increasing sradha and bhakti Hindu Women, with participating in contributing to coaching, training, and socializing related to Hinduism. WHDI's contribution in improving sradha and Bhakti Hindu women in kapuas district is carried out by several activities, namely Dharma Wacana which is carried out routinely on religious days, Persantian to foster concern for ancestral culture, and be able to implementation the values contained in dharma gita. Dharma Tula to provide understanding, and conduct discussions related to Hindu religion and the problems faced. Upakara/Banten training, in order to improve skills in making ceremonial facilities or facilities used in worship. Tirtha Yatra to introduce and increase sradha and Bhakti to Ida Sang Hyang Widhi Wasa through praying at holy places accompanied by chanting the sacred hymns of Hinduism. Socializing the Dana Punia Culture to make Hindu women aware of the importance of Punia, and increasing their understanding that what is classified as Punia is not only material, but can also be non-material